A Call to Action for Musculoskeletal Research Funding: The Growing Economic and Disease Burden of Musculoskeletal Conditions in the United States Is Not Reflected in Musculoskeletal Research Funding. (15th March 2023) - McConaghy, Kara; Klika, Alison K.; Apte, Suneel S.; Erdemir, Ahmet; Derwin, Kathleen; Piuzzi, Nicolas S.
Abstract: As a result of an aging population, musculoskeletal disease is a growing source of health and economic burden in the United States. In 2019, musculoskeletal conditions affected approximately 127.4 million people (more than a third of the U.S. population); they were the top driver of health-care spending in 2016, with an estimated direct annual cost of 380.9 billion. While musculoskeletal conditions represent a substantial and growing burden in terms of prevalence, disability, and health-care costs, National Institutes of Health (NIH) research funding has remained disproportionately allocated to other disease conditions. Therefore, our purpose was to provide an assessment of the current burden of musculoskeletal disease in terms of prevalence, disability, and health-care costs, and compare the changing burden of disease to trends in NIH funding.